A microwave limiter with non‐reciprocal limiting threshold. Issue 2 (22nd January 2023) - Shen, Jian; Liu, Jibin; Lin, Mingtuan; Wu, Zhaofeng; Deng, Shixiong
Abstract: A novel microwave limiter with non‐reciprocal limiting threshold is proposed in this paper to protect the transceiver switch or the transmitter. The directivity of the directional coupler is utilized to make the power of the received signal input to the detection circuit larger than that of the transmitted signal, thereby the detection circuit provides different DC bias voltages to the limiter circuit and changes the threshold level of the limiter diode. The test results show that this limiter has a threshold level of 35 dBm for the transmitted signal and 17 dBm for the received signal, which has a non‐reciprocal limiting threshold for high‐power signals input in both directions. Abstract : A novel microwave limiter with a non‐reciprocal limiting threshold is proposed in this paper, which aims at the problem that the traditional limiter having no directivity is unable to protect the transceiver switch or the transmitter. This non‐reciprocal limiter has a small insertion loss for the transmitted high‐power signal and a good limiting effect for the received high‐power signal.